Thermal management for gas lubricated, high-speed turbomachinery - Olmedo, L.E.; Liu, W.; Gjika, K.; Schiffmann, J. (Applied thermal engineering, 2023)
High-speed turbomachinery is commonly designed to achieve high power densities. Limited space for active cooling results in a challenging thermal management. A thermal modeling approach leveraging modern declarative programming capabilities is presented, yielding an efficient dynamic model capable of real-time simulation while achieving accurate results. These properties enable the inclusion of thermal management strategies in an early stage of the design process. Further, the effect of varying thermal and transport properties of materials and fluids during transient conditions is included and is suggested to yield a high impact on thermal loads and heat evacuation capabilities. The often neglected fluid advection within the system is modeled by integrating a 1D fluid network from MatlabTM SimscapeTM to the thermal model, displaying a significant impact on the temperature estimation for critical parts. The accuracy of the presented model is verified against three gas-bearing supported high-speed turbomachinery experiments for stationary and transient operation. •Dynamic thermal simulation for gas lubricated, high-speed turbomachinery.•Accurate and efficient multi-domain models based on 1D physical networks.•Modeling flexibility with declarative programming paradigm.•Experimental validation from three different gas-lubricated turbomachines.